Seasonal prevalence of child undernutrition and its associated factors in the west Gojjam zone, Ethiopia - Melesse Belayneh Yayeh; Memme Girly Makua (Archives of Public Health)
Abstract Background Seasonal variation in child undernutrition in developing countries such as Ethiopia is a growing concern, which requires policymakers, program directors, and healthcare providers to mitigate this issue. However, there is a dearth of evidence on seasonal variability. Objective We assessed the seasonal prevalence of undernutrition and its associated factors in children in West Gojjam, Ethiopia, in 2024. Methods A longitudinal cross-sectional study was conducted among 844 mother‒child pairs from December 2023 to September 2024. The child anthropometric measurement data were first analysed via the WHO Anthro software version 3.2.2 and then exported to SPSS v. 29 software for further analysis. Results The seasonal prevalence rates of stunting, wasting and underweight were 35.5%, 8% and 17.9% in December; 36.6%, 15.5% and 20.4% in March; 39.2%, 19.2% and 24.6% in June; and 38.2%, 8.1%, and 17% in September, respectively. Childhood waste is significantly associated with factors such as June and March, being male, having unimproved toilet types, having the poorest wealth index, not using contraceptives, not visiting ANC, lacking vitamin A supplementation, and having a larger family size. Factors such as child age, lack of education of mothers, poorest wealth index, poorer wealth index, and low child dietary diversity score were positively associated with stunting in children. Underweight was significantly associated with factors such as June month, being male, age of the child, lack of education of mothers, and the poorer and poorerpoorest wealth index. Conclusions This study revealed high seasonal variation in child undernutrition, a public health problem. The factors significantly associated with child undernutrition were season, male sex, child age, unimproved toilet type, poorer and poorest wealth index, no use of contraceptives, not visiting ANC, not taking vitamin A supplements, larger family size, lack of maternal education, and low child dietary diversity score. Therefore, the design strategies focus on reducing the seasonal burden and addressing factors such as maternal health, household education, and the economic status of the participants.